Hubungan Asupan Protein Nabati dengan Kadar Hemoglobin Pada Wanita Usia Remaja Vegan - Ratna Dewi PS; Winda Trijayanthi Utama; Eniwati Eniwati (Medula, 2019)
Nutrition is one of the determinants of the quality of human resources. Malnutrition can cause failure of physical growth and development of intelligence, reduce work productivity and reduce endurance. The role of essential nutrients is basically not taken seriously by the community, especially adolescents. Insufficient nutritional needs in adolescents occur due to an imbalance in the intake of nutrients in the diet. The diet of adolescents is currently influenced by their environment, such as friends and media in choosing foods that tend to follow trends, coupled with wrong eating habits such as a vegetarian diet, dislike or abstinence from certain types of food. Vegetarian diets have a high risk for the occurrence of deficiency of several nutrients such as protein, iron, calcium, zinc, copper, amino acids, fatty acids, omega 3, omega 6, vitamin D, and Vitamin B12. Protein is the most high-risk nutrient that is deficient in vegetarians and has a function that is essential for the body in the formation of hemoglobin (Hb), protein plays an important role in the transportation of iron in the body. Therefore, a lack of protein intake can cause iron transport to be hampered resulting in iron deficiency resulting in anemia. Several studies have shown that there is a significant relationship between vegetable protein intake and hemoglobin levels.